Optimization of mycobiosynthesis of silver nanoparticles by using Fusarium 4F1 and Trichoderma TRS isolates - Pal, Shital; Hossain, KS (Bangladesh Journal of Botany, 2020)
Silver nanoparticles (Ag-NPs) by mixing silver nitrate (AgNO3) with cell-free filtrate (CFF) of the two fungal isolates viz., Fusarium 4F1 and Trichoderma TrS were synthesized. pH, substrate concentration and incubation period for the production of better quality and quantity of Ag-NPs was optimized. The Ag-NPs by UV-vis spectroscopy were characterized. Between the two fungal isolates, pH levels, AgNO3 concentrations and incubation periods studied, the highest number of spherical shaped, monodispersed and stable Ag-NPs were recorded from Fusarium 4F1 at pH 9, 2 mM AgNO3 and 72 hrs of incubation.